Cold‐stored platelets have better preserved contractile function in comparison with room temperature‐stored platelets over 21 days. Issue Volume 61:Issue S1 (2021)Supplement (16th July 2021) - Nair, Prajeeda M.; Meledeo, Michael A.; Wells, Adrienne R.; Wu, Xiaowu; Bynum, James A.; Leung, Kai P.; Liu, Bin; Cheeniyil, Aswathi; Ramasubramanian, Anand K.; Weisel, John W.; Cap, Andrew P.
Abstract: Although it is well established that transfusion of platelets in cases of severe bleeding reduces mortality, the availability of platelets is hampered by harsh restrictions on shelf life due to elevated risks of microbial contamination and functional losses with room temperature‐stored platelets (RTP) kept at 22°C. In contrast, many recent studies have shown that 4°C cold‐stored platelets (CSP) are able to overcome these shortcomings leading to the recent Food and Drug Administration licensure for 14‐day stored CSP when conventional platelets are unavailable. This work expands the evidence supporting superiority of CSP function by assaying the less explored platelet‐mediated clot retraction of RTP and CSP in either autologous plasma (AP) or platelet additive solution (PAS) for up to 21 days. The results demonstrate that CSP have better preservation of contractile function, exhibiting retraction for up to 21 days in both AP and PAS and forming highly ordered fibrin scaffolds similar to those of fresh platelets. In contrast, RTP stored in AP showed impaired contractile function by Day 5 with no retraction after 10 days, whereas PAS‐stored RTP retained contractile function for up to 21 days. Collectively, these findings support extended storage of CSP and suggest that storage in PAS can mitigate functional losses in RTP.